An inventory of crop wild relatives of the Maltese Islands - Louis Fresta (Genetic Resources and Crop Evolution, 2022)

Correction to: Forest Genetics Research in the Mediterranean Basin: Bibliometric Analysis, Knowledge Gaps, and Perspectives - Bruno Fady; Edoardo Esposito; Khaled Abulaila; Jelena M. Aleksic; Ricardo Alia; Paraskevi Alizoti; Ecaterina-Nicoleta Apostol; Phil Aravanopoulos; Dalibor Ballian; Magda Bou Dagher Kharrat; Isabel Carrasquinho; Marwan Cheikh Albassatneh; et al. (Current Forestry Reports, 2022)

Forest Genetics Research in the Mediterranean Basin: Bibliometric Analysis, Knowledge Gaps, and Perspectives - Bruno Fady; Edoardo Esposito; Khaled Abulaila; Jelena M. Aleksic; Ricardo Alia; Paraskevi Alizoti; Ecaterina-Nicoleta Apostol; Phil Aravanopoulos; Dalibor Ballian; Magda Bou Dagher Kharrat; Isabel Carrasquinho; Marwan Cheikh Albassatneh; et al. (Current Forestry Reports, 2022)
Purpose of Review Recognizing that in the context of global change, tree genetic diversity represents a crucial resource for future forest adaptation, we review and highlight the major forest genetics research achievements of the past decades in biodiversity-rich countries of the Mediterranean region. For this, we conducted a bibliometric analysis of the scientific literature spanning the past thirty years (1991–2020). Putting together the representative regionwide expertise of our co-authorship, we propose research perspectives for the next decade. Recent Findings Forest genetics research in Mediterranean countries is organized into three different scientific domains of unequal importance. The domain “Population diversity and Differentiation” related to over 62% of all publications of the period, the domain “Environmental conditions, growth and stress response” to almost 23%, and the domain “Phylogeography” to almost 15%. Citation rate was trending the opposite way, indicating a strong and sustained interest in phylogeography and a rising interest for genetics research related to climate change and drought resistance. The share of publications from Asia and Africa to the total within the Mediterranean increased significantly during the 30-year period analyzed, reaching just below 30% during the last decade. Summary Describing poorly known species and populations, including marginal populations, using the full potential of genomic methods, testing adaptation in common gardens, and modeling adaptive capacity to build reliable scenarios for forest management remain strategic research priorities. Delineating areas of high and low genetic diversity, for conservation and restoration, respectively, is needed. Joining forces between forest management and forest research, sharing data, experience, and knowledge within and among countries will have to progress significantly, e.g., to assess the potential of Mediterranean genetic resources as assisted migration material worldwide. Introductory quote: Let us collect with care the facts we can observe, let us consult experience wherever we can, and when this experience is inaccessible to us, let us assemble all the inductions which observation of facts analogous to those which escape us can furnish and let us assert nothing categorically; in this way, we shall be able little by little to discover the causes of a multitude of natural phenomena, and, perhaps, even of phenomena which seem the most incomprehensible... J.B. de Lamarck (Philosophie zoologique, 1809), cited by O. L anglet (1971).